A LITERATURE REVIEW: FACTORS RELATED TO THE PASUNG AMONG PEOPLE WITH MENTAL ILLNESS: DOI: https://doi.org/10.35654/ijnhs.v2i2.95 - Angelina Roida Eka; Novy Helena Catharina Daulima (Alta Dharma Publisher, 2019)
Physical restraint and confinement (pasung) by families of people with mental illness is known to occur in many parts of the world Pasung is a common human right violation on people with mental illness found on every country in the world especially in developing countries like Indonesia. In Indonesia the term pasung refers to the physical restraint or confinement of